ANALISIS PENGUNGKAPAN INDIKATOR KINERJA DALAM SUSTAINABILITY REPORTING PERUSAHAAN PERTAMBANGAN BESAR DI INDONESIA - Ananda Nichola; Aditya Septiani (Diponegoro Journal of Accounting, 2019)
The purpose of this study is; first, to analyze the disclosure’s level of performance indicators in sustainability reporting of large mining companies in Indonesia. Second, to find out whether the disclosure of performance indicators is already in accordance with the Global Reporting Initiative (GRI) G4 guidelines.This study used secondary data from sustainability disclosure database and each of company’s website. Content analysis method is used to analyze 21 sustainability reports of seven large mining companies in Indonesia during 2014-2016.This study finds that; first, the disclosure’s level of performance indicators in the sustainability reports has been quite high because there are four companies that have a disclosure percentage of >50% during the 2014-2016 period. Second, the disclosure’s level of performance indicators in the sustainability reports is sufficient in accordance with the GRI G4 guidelines. However, there are still some categories that are slightly disclosed (<50%) and need to be improved. Meanwhile, the development of performance indicators disclosure is fluctuating from 2014-2016.